Pengaruh Word Of Mouth, Kepercayaan, Harga Dan Brand Awareness Terhadap Niat Beli Smartphone Samsung - Reza Avia Pradana; Gunawan, Benny (Innovative: Journal Of Social Science Research, 2024)
Along with the development of technology in the current era of globalization in which there is a demand for rapid exchange of information between regions and even between countries which makes telecommunication media very important so that information travels very quickly. The purpose of this research is to see if there is any influence between Word of Mouth, trust, price, and brand awereness on people's purchase intention for Samsung products. The population in this study are all people who know and use Samsung smartphones who are domiciled in West Jakarta, whose number is unknown. The sample in this study was taken using the NonProbability Sampling method using the purposive sampling technique of 100 respondents aged 17-35 years and over. The analytical method used is multiple linear regression analysis to determine the direct and indirect effects between variables. The results showed that word of mouth, trust, price, and brand awereness variables had a positive influence on the purchase intention variable for Samsung smartphones. Future research is expected to expand the range of regions and add other variables related to purchase intention.